Impact Water Supply and Sanitation Community-Based Toward Behavior Change Environmental Society in the Middle District of Kampar Kiri Kampar Regency (Jurnal Kajian Lingkungan, 2013)
Clean water is an absolute necessity humans. Without water, humans can not hidup. Disamping that humans also require sanitation facilities to accommodate the manure so it does not pollute the environment and resources bersih. Air water and sanitation in rural areas is closely related to knowledge, habits (culture), and the role of community leaders, so that with all three of these factors can change peoples behavior in the countryside. Problems shown in this study is the change in peoples behavior toward the environment in rural areas in particular about clean water and sanitation, which is measured using three variables: knowledge, behavior (culture), and the role of community leaders. This study uses qualitative and quantitative approaches, by distributing questionnaires to people in three villages namely Main Village Works, Karya Bhakti, and Livelihoods, and analyzed using path analysis to determine the relationship between variables. The analysis showed no association between faktorpengetahuan, culture, and community leaders to change their behavior in the main village of Karya, and Karya Bhakti. However, factor in the Village Livelihood public figures do not have a relationship with behavior change in rural communities tersebut. Sehingga be in the know that the community leaders in the village of Livelihoods lesser role, and in the main village of Karya Bhakti work and all play factors.Kata Kunci : Water and Sanitation, knowledge, habit, community leaders, Behavior onEnvironment.